A novel method for assessing the toxicity of silver nanoparticles in Caenorhabditis elegans. (February 2017) - Luo, Xun; Xu, Shengmin; Yang, Yaning; Zhang, Yajun; Wang, Shunchang; Chen, Shaopeng; Xu, An; Wu, Lijun
Abstract: At present, nanotechnology has been producing nanoscale materials with unprecedented speed. Nanomaterials could be inevitably released into the environment owing to their widespread use, and their potential toxicity has caused a great concern. With regard to assessment of nanomaterial toxicity, many studies probably don't truly reflect their toxicity, because the nanoparticles were not stable and uniformly dispersed in the medium. In the present study, the semi-fluid nematode growth gelrite medium (NGG) was used to achieve better distribution of silver nanoparticles (AgNPs). We aimed to evaluate the toxicity of AgNPs in three different culture methods, such as the NGG, nematode growth medium (NGM) and K-medium (KM). Our transmission electron microscopy, hydrodynamic diameter, and inductively coupled plasma-atomic emission spectrometry results demonstrated that AgNPs homogeneously and stably dispersed in NGG compared to that in liquid KM. Furthermore, the conventional toxicity end points, such as body length, fecundity, lifespan, population growth, germline cell apoptosis, reactive oxygen species, and mitochondrial membrane potential were used to assess the toxicity of AgNPs to Caenorhabditis elegans ( C. elegans ) in NGG, NGM and KM. Our results showed that the toxicity of AgNPs obtained in the NGG test medium was much higher than that in the standard NGM and KM. In addition to the improved dispersion of nanoparticles, NGG also offered advantages for long-term studies and likely provided a convenient nematode toxicity testing method. These results revealed that the NGG test medium was a suitable and sensitive culture method for the evaluation of AgNPs toxicity using C. elegans . Graphical abstract: Highlights: A semi-fluid NGG method for assessing toxicity of AgNPs using C. elegans is proposed. AgNPs affect germ cell apoptosis, reproductive ability and lifespan of C. elegans. The semi-fluid NGG has more advantages and sensitivity for evaluating the toxicity of AgNPs using C. elegans. For semi-fluid NGG, the population growth assay is firstly applied to detect ecological toxicity of AgNPs.